GROWTH RATE OF CORAL Acropora intermedia ON MEDIA CORAL TRANSPLANTATION IN SIRONJONG GADANG ISLAND SOUTH COAST WEST SUMATERA - Rio Aprialis Safitra; Syahril Nedi; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from January to March 2016 in Sironjong Gadang Island. The island is located in the sub-district of Koto XI, in the region of South Coast Regency of West Sumatera Province. The aimed of this research was to determine the growth and the survival rate of Acropora intermedia plantations. Experimental methods were applied by measuring the growth rate and counting the survival rate of the coral transplants. Besides, the surrounding parameters of water quality were also measured in the field. The result showed that the lateral growth of the transplant was faster than the vertical one; the values were 0.748 cm and 1.512 cm consecutively. In addition, the survival rate reaches 90 %, however, bleaching coral and dead coral with algae was also found in the first 20 days of observation.Keyword: Acropora intermedia, Growth Rate, Sironjong Gadang Island